Performance investigation of low power radio duty cycling MAC for resource constrained WSN - Rajesh Shyamala Devi, B; George, A; K. Thomas, Aby (International Journal of Engineering and Technology, 2018)
Wireless Sensor Networks (WSN) are the corner stone of next generation communication networks. The OSI Layer 2 and Layer 3 communication technologies of the WSN are the important aspects in communication and networking research. The protocols and standards of WSN in different layers are already well defined. In this article, we evaluate the Layer 2 mechanisms which meet the special demands of WSNs for resource constrained applications. Large number of WSN devices need to be deployed in a typical environmental monitoring use cases. In this work we consider a use case of sensors and actuators in a small geographical region. For this a short range communication technology such as IEEE 802.15.4 is considered. Various type of sensors are deployed in the same region, in this cases effective MAC mechanism is required to effectively allocate the channel resource among these devices. The main concentration of this article is about the energy consumption of WSN devices. As the devices and network is resource constrained, energy efficient hardware’s, communication networking protocols and suitable software implementations are required. As far as the energy efficient protocols are considered MAC mechanisms is one of the very important processes, where suitable energy efficient mechanisms need to be selected. In the recent literatures showed that Contiki MAC is one of the suitable MAC layer implementation with dedicated Radio Duty Cycling Layer (RDC) which conserves the WSN nodes battery power. In this article we analyze the state of the art Layer 2 mechanisms for WSN in environmental monitoring use case, by a theoretical analysis and simulation based experiments.